Alternative complement pathway component Factor D contributes to efficient clearance of tissue debris following acute CCl4-induced injury. Issue 1 (March 2015) - Cresci, Gail A.; Allende, Daniela; McMullen, Megan R.; Nagy, Laura E.
Highlights We examine which complement activation pathway is involved for timely liver recovery following an acute toxic injury. We utilized mice deficient in C1qa, C4 and Factor D, lacking the classical, classical/MBL, and alternative pathways of complement activation. Factor D-deficient mice had worse liver injury compared to other genotypes. Factor D-deficient mice were unable to adequately clear injured tissue. We demonstrate the importance of the alternative complement pathway in facilitating opsonization of damaged tissue for a timely reparative process following an acute toxic liver injury.